Palliative care for people with substance use disorders: a qualitative study of the experiences of rural primary care providers - Layale Tayba; Beatriz Cuesta-Briand; Kirsten Auret; Mathew Coleman (BMC Palliative Care)
Abstract Background In Australia, substance use disorders disproportionately affect people living in rural and remote areas. Patients with substance use disorders who receive palliative care have complex, often unmet, end-of-life needs. There is scarce evidence on the management of patients with substance use disorders in palliative care, and there is no consensus on the model of care to assist general practitioners manage their patients. This is particularly salient for general practitioners in rural areas, who provide most of the palliative care to their patients. Methods This qualitative study explored the experiences of providing palliative care to patients with a substance use disorder among general practitioners in regional Western Australia. Data were collected through semi-structured interviews and subjected to thematic analysis. Results A total of 12 interviews were conducted. Three main themes were identified: (1) a value-laden space; (2) substance-specific attitudes and practice; and (3) barriers to managing substance use disorders in palliative care. It was found that General practitioners’ personal values shape attitudes towards substance use, and impact on the management of substance use disorders for patients receiving palliative care. Attitudes and palliative care practice vary depending on the type of substance of concern. Perceived barriers to recognition and management of substance use in palliative care included patient, health professional, health system and societal factors. Conclusions Early recognition and intervention for people presenting with substance use disorders in palliative care settings may improve patient quality of living and make managing life-limiting illness safer and more effective. In rural settings in Australia, care is often provided by general practitioners yet despite their whole of person approach to medicine and capacity to manage complexity and multimorbidity, challenges persist in optimising the care of substance use disorders in palliative care. This study provides insight into areas for further research, the potential for the development of clinical practice standards and guidelines in this complex area of palliative care.